The Association of the Familistère at Guise (L'Aisne), France : a lecture ... delivered september 8th, 1881, in the hall of the Museum of industry, at Lausanne - Godin, Jean-Baptiste André (1817-1888)
Translated from "Le Devoir" of september 18, 1881, by Edward Vansittart Neale